2015
DOI: 10.1159/000380764
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Electromagnetic Field Exposure Enhances Extracellular Trap Formation by Human Neutrophils through the NADPH Pathway

Abstract: Low-frequency (LF) electromagnetic fields (EMFs) are abundantly present in modern society, and the potential biological consequences of exposure to these fields are under intense debate. Immune cells are suggested as possible target cells, though a clear mechanism is lacking. Considering their crucial role in innate immune activation, we selected an ex vivo exposure set-up with human neutrophils to investigate a possible correlation between neutrophil extracellular trap (NET) formation and LF EMF exposure. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
(50 reference statements)
1
17
2
1
Order By: Relevance
“…Wortmannin is a cell-permeable fungal metabolite that acts as a potent, selective and irreversible inhibitor of phosphatidylinositol 3-kinase (PI3K) which is required for autophagy [ 46 , 47 ]. Wortmannin (Sigma-Aldrich) was used in a concentration of 100 nM in the in vitro tests [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Wortmannin is a cell-permeable fungal metabolite that acts as a potent, selective and irreversible inhibitor of phosphatidylinositol 3-kinase (PI3K) which is required for autophagy [ 46 , 47 ]. Wortmannin (Sigma-Aldrich) was used in a concentration of 100 nM in the in vitro tests [ 48 , 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the initial phases of wound healing, neutrophils and pro-inflammatory M1 type macrophages play a crucial role in the protection from pathogens and in the clearance of cell debris. As already mentioned, exposure of neutrophils to PEMFs promotes the formation of NETs and NETosis ex vivo ( 32 ), an effect that could potentiate the initial response. Removal of pathogens through an effective action of neutrophils, followed by clearance of dead neutrophils by macrophages, is a prerequisite for the subsequent control of inflammation and repair phases.…”
Section: Emf and Immunomodulation In Wound Healingmentioning
confidence: 88%
“…The role that neutrophils play in immune response, their high reactivity, mobility, and sensitivity make them putative targets for investigating possible cell modulation effects by ELF-EMF exposure. The first study investigating ELF-EMF impact on NET formation, ex vivo , was performed by the group of Golbach et al and showed that ELF-EMF (multifrequency “Immunent” signal; 300 µT; 1–4 h) alone was unable to induce NETs ( 32 ). However, the ELF-EMF was able to significantly enhance NET formation in freshly isolated peripheral blood neutrophils that were pre-activated with phorbol 12-myristate 13-acetate (PMA).…”
Section: Effects Of Emfs On Innate Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Today, we know that autophagy is an essential cytosolic clearance mechanism that not only helps to maintain normal cell homeostasis, but is also a critical regulator of the intracellular immune system [6] . The Journal of Innate Immunity has recently issued a couple of articles dealing with this area of research [7][8][9] . In this volume, there is a paper by Katarina Nurmi et al [10] on a study reporting that hemin and cobalt protoporphyrin can inhibit NLRP3 inflammasome activation by enhancing autophagy.…”
mentioning
confidence: 99%